Financial Performance Analysis of PT. Pertamina, Tbk for the 2020–2023 Period - Mutmainna Andi Sudirman; Andi Jenni Indriakati; Nurul Aini (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
This study aims to evaluate the financial performance of PT. Pertamina, Tbk for the period 2020–2023 using liquidity, profitability, and activity ratios. The research utilizes a descriptive quantitative method by analyzing the company's financial reports obtained from official sources. The liquidity ratio is measured using the Current Ratio, profitability using Return on Assets (ROA), and activity using Total Assets Turnover (TATO). The findings show that the company experienced significant fluctuations in all three ratios during the observed period, reflecting the influence of external economic factors and internal financial strategies. The average Current Ratio indicates moderate liquidity, ROA reflects sufficient profitability with room for improvement, and TATO reveals increasing asset efficiency up to 2022 before slightly declining in 2023. Overall, the study highlights the financial resilience and areas needing improvement for PT. Pertamina, Tbk amidst global and domestic challenges